2020
DOI: 10.1080/23802359.2020.1736963
|View full text |Cite
|
Sign up to set email alerts
|

The complete chloroplast genome of Caryopteris incana (Lamiaceae) and phylogenetic analysis

Abstract: The species Caryopteris incana is a traditional Chinese herbal medicine and ornamental plant. The first complete plastid genome sequences of C. incana reported here was 151,687 bp long, with the large single copy (LSC) region of 83,178 bp, the small single copy (SSC) region of 17,225 bp and two inverted repeats (IRa and IRb) of 25,642 bp. The plastome contained 114 genes, including four ribosomal RNA genes, 30 transfer RNA genes, and 80 protein coding genes. The overall GC content was 38.2%. Result from phylog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…The analysis demonstrated that the M. sikkimensis chloroplast genome spanned a length of 149,428 bp, and it featured the circular quadripartite typical of chloroplast genomes, consisting of the LSC, SSC, and a pair of IR regions. Gene annotation indicated that the genome contains 112 genes, which include 78 protein-coding genes, 30 tRNA genes, and 4 rRNA genes, which is consistent with the genomic structure and gene quantity observed in the chloroplasts of other species within the Boraginaceae family [47][48][49][50][51]. Introns were crucial for the regulatory mechanisms that control gene expression.…”
Section: Discussionsupporting
confidence: 68%
“…The analysis demonstrated that the M. sikkimensis chloroplast genome spanned a length of 149,428 bp, and it featured the circular quadripartite typical of chloroplast genomes, consisting of the LSC, SSC, and a pair of IR regions. Gene annotation indicated that the genome contains 112 genes, which include 78 protein-coding genes, 30 tRNA genes, and 4 rRNA genes, which is consistent with the genomic structure and gene quantity observed in the chloroplasts of other species within the Boraginaceae family [47][48][49][50][51]. Introns were crucial for the regulatory mechanisms that control gene expression.…”
Section: Discussionsupporting
confidence: 68%
“…In this study, plastomes of 50 taxa were newly sequenced and 61 taxa were reassembled from the sequence read archive (SRA) database; others were acquired from previous studies [ 66 , 67 , 206 , 207 ] or downloaded from NCBI ( https://www.ncbi.nlm.nih.gov ; Additional file 8 : Table S3). In total, the ingroup sampling included 170 taxa (175 accessions), 79 genera, and represented all 15 currently recognized tribes and all 12 subfamilies within Lamiaceae [ 19 , 51 ].…”
Section: Methodsmentioning
confidence: 99%
“…All the newly sequenced and annotated plastomes in the present study were submitted to the National Center for Biotechnology Information (NCBI) database with accession numbers MT473738-MT473786 (Table 1). Other plastomes analyzed were acquired from previous studies [66,67,206,207] or downloaded from NCBI (https://www.ncbi.nlm.nih.gov; Additional file 8; Table S3). The alignments and ML tree are deposited at TreeBase with study #S26639 (http://treebase.org/treebase-web/phylows/ study/TB2:S26639?x-access-code=bb02a4c5bc226f4604690ea0f21ccd41 &format=html) [226].…”
Section: Supplementary Informationmentioning
confidence: 99%
See 1 more Smart Citation